ChemInform Abstract: Nanoporous Gold: Understanding the Origin of the Reactivity of a 21St Century Catalyst Made by Pre‐Columbian Technology. Issue 51 (December 2015) - Biener, Juergen; Biener, Monika M.; Madix, Robert J.; Friend, Cynthia M.
Abstract: Review: 105 refs.